Experimental Investigation of Progressive Failure Processes Using 3D Acoustic Emission Tomography - Cheng, Yan; Hagan, Paul; Mitra, Rudrajit; Wang, Shuren; Yang, Hong-Wei (Frontiers in Earth Science, 2021)
In this paper, the potential of 3D acoustic emission (AE) tomography technique in demonstrating fracture development and delineating stress conditions was examined. Brazilian tests and uniaxial compression tests were monitored by 3D AE tomography. AE counts, AE source locations and 3D tomographic images of locally varying velocity distributions were analyzed along with stress and strain measurements. Experimental results revealed two distinct failure processes between Brazilian tests and uniaxial compression tests indicated by differences in AE counts, source locations and the temporal variation of velocity. Furthermore, the development of micro-cracks showed by the results correlated well with theoretical analysis and experimental observations. Additionally, stress patterns, failure modes and final failure planes were indicated by AE locations and velocity tomography. Three-dimensional velocity tomographic images indicated the anisotropy of samples caused by stresses as well. These results confirm the usefulness of AE tomography as a method to monitor stress induced failure and the potential of AE tomography for delineating stress conditions and predicting rock failure.